A Framework for Marketing Management - Philip Kotler (Pearson Education Limited, 2009)
A Framework for Marketing Management is dedicated to helping companies, group, and individuals adapt their marketing strategies and management ti the marketplace of the twenty-first century. This book discusses about marketing management, that is discussed in seven chapter. The first chapter discusses about understanding marketing management encompass defininf marketing for the twenty-first century, developing and implementing marketing strategies, understanding markets, markets demand, and the marketing enviroment. The second chapter discuss about connecting with customers, encompass creating customer value, satisfaction and loyalty, analyzing consumer markets, analyzing business markets, and about identifying market segments and targets. The third chapter discuss about building strong brands, encompass creating brand equity, crafting the brand positioning and dealing with competition. The fourth chapter discuss about Shaping the marker offerings, encompass setting product strategy and marketing through the life cycle, designing and managing services, also about developing pricing strategies and program. The fifth chapter about delivering value, encompass designing and managing integrated marketing channels, and managing retaling, wholesaling, and logistics. The sixth chapter discuss about communicating value, encompass desingning and managing integrated marketing communication, managing mass communication and managing personal communications. The last chapter discuss creating successfull long-term growth, encompass managing marketing in the global economy.